'A Peacock's Plume Among a Pile of Geese Feathers': Rosa Praed in the United States. Issue 1 (8th May 2014) - Carter, David
<x content-type="archive" xml:space="preserve">Abstract</x> Rosa Praed has been claimed as 'the first Australian-born novelist to achieve a significant international reputation.' Almost certainly, she was the first Australian-born novelist to be published in the United States, although she was in England by the time her first novel appeared in America in 1883. Of Praed's forty-seven published works, twenty-five appeared in American editions in the three decades from 1883 to 1915, including twenty-four of her thirty-eight novels in more than forty separate editions. In the years either side of the century's turn, she was among the best known Australian writers in America, alongside Louis Becke and Rolf Boldrewood.